Modern Methods of Furniture Design in the Interior of a Building of a Preschool Educational Organization - Abdiyev Hamza Jalalovich; Tashmatova Xosiyat Sidikovna (Genius Journals, 2022)
This article is aimed at studying modern methods of furniture design in the interior of the premises of a preschool educational organization (kindergartens) and developing proposals for their application in practice.
Keywords: preschool furniture; furniture for kindergartens; equipment for child care; furniture for preschoolers